ASSESSING BUILDING TYPES TO TRACE THE EVOLUTION OF URBAN FORM - Prifti, Jonila (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Since Tirana became Albania’s capital, its urban transformation has reflected the ambitions and ideologies of successive governing regimes. This study examines the city’s architectural and morphological evolution, analyzing how political, social, and economic shifts have influenced its urban fabric from the 1920s to the present. The research employs a historical and morphological analysis of Tirana’s urban form, integrating insights from urban theorists such as Whitehand, Oliveira, and Dovey. It reconstructs the city’s development by categorizing architectural typologies across five key historical periods. Archival research, spatial mapping, and case study analysis of representative buildings and planning policies form the core of the study’s methodological approach. The study reveals that Tirana’s urban transformation is marked by phases of expansion, socialist central planning, and post-communist redevelopment. Each governing regime has imposed distinct planning strategies, ranging from rigid, state-controlled designs to contemporary neoliberal densification policies. Recent urban planning documents advocate for extensive demolition and reconstruction, often at the expense of traditional urban structures, raising concerns about heritage preservation and socio-spatial justice. This research provides a critical reassessment of Tirana’s urban development by integrating historical and contemporary urban planning perspectives. It highlights the city’s transition from a fragmented town to a contested urban landscape shaped by ideological shifts, offering new insights into how political narratives manifest in architectural and planning practices. The study underscores the need for a balanced approach that preserves historical identity while accommodating future urban growth.